1997
DOI: 10.1039/a607359j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Rayleigh Light Scattering of Acid Chrome Blue K by Proteins and Protein Assay by the Scattering Technique

Abstract: Rayleigh light scattering of Acid Chrome Blue K (ACBK) is enhanced greatly by proteins. Based on this, a method for protein assay in aqueous solution was developed. This assay matches the sensitivity of the colorimetric dye-binding method with a linear range of 0.136-10.88 micrograms ml-1. The measurements can be made easily on a common fluorimeter. The reaction between ACBK and proteins is completed in 2 min and the scattered light signal is stable for at lest 3 h. Protein-to-protein variability is encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Since Pasternack developed a resonance light scattering (RLS) technique with a common spectroflurimeter (12,13), this technique has been widely applied to determine nucleic acids (14)(15)(16) and proteins (17)(18)(19)(20). The RLS technique is based on the following phenomenon: when the wavelength of the incident beam is close to the absorption band of molecular particles which exist as aggregates, the Rayleigh scattering intensity of some wavelengths will be much higher than normal light scattering (21).…”
Section: Introductionmentioning
confidence: 99%
“…Since Pasternack developed a resonance light scattering (RLS) technique with a common spectroflurimeter (12,13), this technique has been widely applied to determine nucleic acids (14)(15)(16) and proteins (17)(18)(19)(20). The RLS technique is based on the following phenomenon: when the wavelength of the incident beam is close to the absorption band of molecular particles which exist as aggregates, the Rayleigh scattering intensity of some wavelengths will be much higher than normal light scattering (21).…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al (9)(10)(11) used this technique for protein assay, and subsequently this method has attracted the attention of many researchers (12)(13)(14)(15).…”
mentioning
confidence: 98%
“…This technique is an important tool for biomolecule analysis, although the enhancement of resonance light scattering requires the aggregation of dyes on nucleic acids. Ma et al (14,15) and Wei et al (16) found that some small molecules that do not selfaggregate can also produce enhanced light scattering signals when they react with proteins. This type of scattering is not resonance light scattering, but Rayleigh light scattering (RLS) 2 (14).…”
mentioning
confidence: 98%